IMPLEMENTASI MODEL PEMBELAJARAN MAKE A MATCH UNTUK MENINGKATKAN MOTIVASI PESERTA DIDIK PADA MATERI PANTUN BAHASA INDONESIA DI MI UNGGULAN IBNU SINA - Jamilah , Siti Saniatul; Hasanah, Siti Uswatun; Huda, Samsul (Lembaga Penelitan dan Pengabdian Masyarakat Institut Agama Islam Sahid, 2024)
The Make a match learning model is a learning model that can increase students' learning motivation, because this model can create a learning atmosphere that is fun and easy to understand. The aim of this research is to increase students' learning motivation. The research method used in this research is qualitative. The data source for this research is secondary data in the form of interviews with Indonesian language subject teachers. The results of this research indicate an increase in students' learning motivation in taking Indonesian language lessons.